Mammalian Taste Bud Cells Utilize Extragemmal 5-Hydroxy-L-Tryptophan to Biosynthesize the Neurotransmitter Serotonin - Pan, Hong-Ru; Tian, Miao; Xue, Jian-Bo; Li, Song-Min; Luo, Xiao-Cui; Huang, Xiao; Chen, Zhen-Huang; Huang, Liquan (Frontiers in Cellular Neuroscience, 2018)
Serotonin or 5-hydroxytryptamine (5-HT) is an important neurotransmitter that is found in mammalian taste buds and can regulate the output of intragemmal signaling networks onto afferent nerve fibers. However, it is unclear how 5-HT is produced, synthesized locally inside taste buds or absorbed from outside sources. In this study, we attempt to address this question by delineating the process of possible 5-HT biosynthesis within taste buds. First, we verified that the rate-limiting enzyme tryptophan hydroxylase (TPH2) responsible for converting L-tryptophan into the intermediate 5-hydroxy-L-tryptophan (5-HTP) is expressed in a subset of type II taste bud cells whereas the enzyme aromatic amino acid decarboxylase (AADC) capable of converting 5-HTP into 5-HT is found in type III taste bud cells. And abolishment of TPH2 did not affect the production of intragemmal 5-HT or alter taste bud cell types; the mutant mice did not show any changes in behavioral responses to all five primary taste qualities: sweet, umami, bitter, salty and sour. Then we identified that 5-HTP as well as AADC are abundant in type III taste bud cells; and application of an AADC inhibitor significantly blocked the production of 5-HT in taste buds. In contrast, administration of an inhibitor on serotonin reuptake transporter had minimal impact on the 5-HT amount in taste buds, indicating that exogenous 5-HT is not a major source for the intragemmal transmitter. Taken together, our data indicate that intragemmal serotonin is not biosynthesized de novo from tryptophan; instead, it is produced by AADC-mediated conversion of 5-HTP absorbed from the plasma and/or nerve fibers into 5-HT. Thus, our results suggest that the overall bodily 5-HTP level in the plasma and nervous system can regulate taste buds’ physiological function, and provide an important molecular mechanism connecting these peripheral taste organs with the circulatory and nervous systems.